Teachers’ and Students’ Perception about Blended Learning: A Case Study of the University of Okara - Muhammad Tahir Khan Farooqi, Shehzad Ahmed, Salma Waheed (PJDOL, 2023)
The study was designed to investigate the perception of teaching faculty and learners regarding blended learning, i.e. the mixture of classroom and computer-equipped learning. The population of the study was comprised of students and teachers of university of Okara.